2001
DOI: 10.1021/bi002321t
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Regulates S-Nitrosylation, Denitrosylation, and Activity of Tissue Transglutaminase

Abstract: Nitric oxide (NO) and related molecules play important roles in vascular biology. NO modifies proteins through nitrosylation of free cysteine residues, and such modifications are important in mediating NO's biologic activity. Tissue transglutaminase (tTG) is a sulfhydryl rich protein that is expressed by endothelial cells and secreted into the extracellular matrix (ECM) where it is bound to fibronectin. Tissue TG exhibits a Ca(2+)-dependent transglutaminase activity (TGase) that cross-links proteins involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 34 publications
3
107
0
Order By: Relevance
“…Other similar examples have recently been uncovered, including the preferential reactivity of GSNO (versus CysNO) with E. coli OxyR (43), and the stereoselective inhibition of T-type calcium channels by l-versus d-CysNO (44). NaAD ϩ -dependent Snitrosylation of Qns1p points further to the importance of allostery in control of S-nitrosylation, and it is notable that S-nitrosylation of hemoglobin (45), serum albumin (46), tissue transglutaminase (47), and the ryanodine receptor (48) are also modulated allosterically (by O 2 , fatty acid, Ca 2ϩ and Ca 2ϩ -calmodulin, respectively). More generally, allosteric effectors are shown to have profound consequences on efficiency of Snitrosylation and thus may be underappreciated determinants of SNO reactivity.…”
Section: Discussionmentioning
confidence: 84%
“…Other similar examples have recently been uncovered, including the preferential reactivity of GSNO (versus CysNO) with E. coli OxyR (43), and the stereoselective inhibition of T-type calcium channels by l-versus d-CysNO (44). NaAD ϩ -dependent Snitrosylation of Qns1p points further to the importance of allostery in control of S-nitrosylation, and it is notable that S-nitrosylation of hemoglobin (45), serum albumin (46), tissue transglutaminase (47), and the ryanodine receptor (48) are also modulated allosterically (by O 2 , fatty acid, Ca 2ϩ and Ca 2ϩ -calmodulin, respectively). More generally, allosteric effectors are shown to have profound consequences on efficiency of Snitrosylation and thus may be underappreciated determinants of SNO reactivity.…”
Section: Discussionmentioning
confidence: 84%
“…SNO-proteins in vivo would be exposed to the effects of proteolytic enzymes (30) and calcium, which is released from intracellular stores. We have previously shown that tissue transglutaminase is regulated by poly-S-nitrosylation and that Ca 2ϩ determines the stoichiometry of S-nitrosylation (28). As shown in Fig.…”
Section: See Also Triiodide Cautionary Notes In Si Text)mentioning
confidence: 88%
“…Accordingly, bond dissociation energies of RSNO are reported to vary from Ϸ22 to 32 kcal⅐mol Ϫ1 (6,26), and the dissociation constants of FeNO can vary by a factor of Ͼ10 6 (13,23,24), translating to intrinsic FeNO/SNO lifetimes ranging from seconds to years. Environmental factors that have been reported to influence SNO stability and reactivity, directly or through elicited conformational changes in proteins, include pH (low and high) (5,6,20,26), metal ions (Ca, Mg, Cu, and Fe) (6,14,20,27,28), nucleophiles (ascorbate, thiolate, and amine) (6,13), local hydrophobicity (denaturants) (29), oxidants and reductants (6,19), proteolytic enzymes (30), alkylators (31), O 2 tension (5,32), and various intramolecular interactions (H-bonding, S-, N-, O-coordination, and aromatic residue interactions) (6,16,20,22,(33)(34)(35)(36). Many of these factors also affect FeNO stability (17,23,24).…”
mentioning
confidence: 99%
“…Both TG2 and FXIII transglutaminase activities are also regulated by nitric oxide. Of the 18 free cysteine residues in TG2, 15 can be nitrosylated and denitrosylated in a calcium-dependent manner, resulting in enzymatic inhibition or activation, respectively (97). Factor XIIIa is similarly inhibited by NO (98).…”
Section: Transglutaminases and Arterial Remodelingmentioning
confidence: 99%